The prevalence of apical periodontitis and endodontic treatment in two coagulation disorders (Research, Society and Development, 2021)
Coagulation disorders such as hemophilia and Von Willebrand’s disease are characterized by changes in inflammatory responses and tissue repair. Inflammatory responses could be involved in the destruction of the periradicular bone and/or interfere with repair mechanisms following endodontic treatment. The aim of this study was to evaluated the prevalence of apical periodontitis (AP) and endodontic treatment in two coagulation disorders. Panoramic radiographs (106 from the study and 106 from the control groups) were  examined for the presence of AP lesions in untreated and root canal-treated teeth. The number of teeth and the prevalence of root canal treatments were also recorded. Two endodontists evaluated all items separately. Statistical analyses were performed using the Statistical Package for Social Science (SPSS), version 21.0 (IBM, Armonk, NY, USA) and the level of statistical significance was established at 5% (p < 0.05). The prevalence of AP was not significantly different between the study and control groups (p=0.574). However, the comparative analyses between them revealed statistically significant differences in variables such as the presence of endodontic treatment (p=0.007), adequate filling (p=0.014), endodontic treatment with AP (p